This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let's say, y=x^x
thus, lny =ln(x^x)
ln y = x.lnx
By differentiating,
(1/y)*dy/dx = lnx + 1 (chain rule and uv for second part)
Thus, dy/dx= y*((lnx)+1)
Because y=x^x,
The result is (x^x)*((lnx)+1)
Now plug in values
( x x ) ′ = x x − 1 + x x l o g ( x ) ∣ ( x = 1 ) = 1
Not quite - you need to account for the x that's being raised to the power x, and log(1) = 0.
Problem Loading...
Note Loading...
Set Loading...
f ( x ) = x x = e x ln ( x ) ∴ f ′ ( x ) = ( ln ( x ) + 1 ) e x ln ( x ) = ( ln ( x ) + 1 ) x x ⟹ f ′ ( 1 ) = ( ln ( 1 ) + 1 ) × 1 1 = 1